A comparative study between two percentage of occurrence methodologies for computing ionospheric scintillation statistics. Issue 3 (1st August 2020) - Paul, B.; De, B.K.; Saha, K.; Guha, A.
Abstract: This study presents a detailed comparative analysis of the two widely used percentage of occurrence methodologies used to compute the statistics of ionospheric scintillation activity based on the data of a Global Positioning System (GPS) Ionospheric Scintillation and (TEC) Total Electron Content Monitor (GISTM) receiver located at the northern Equatorial Ionization Anomaly (EIA) crest region Agartala (23.76°N, 91.26°E) of the Indian subcontinent, during 2012–2015 of the rising, peak and declining solar activity periods of solar cycle-24. Both the methodologies, one based on the number of scintillation event days and another based on the number of scintillation events, provide the correct and similar scintillation statistics qualitatively. But a rigorous comparative study shows significant quantitative differences between the statistics obtained by the two methodologies. The variation of scintillation occurrence obtained by the two methodologies with solar and geomagnetic activity shows that the methodology based on the number of scintillation events provides more accurate and physically acceptable results. Though this fact may be familiar to some researchers but still the scientific community has been using both the methodologies in parallel to compute scintillation statistics. So, from this comparative analysis future researchers can get a clear scenario of the advantages and disadvantages of these methodologies over one another before adopting any one of those for computing scintillation statistics. We also want to highlight the issue to the scientific community to come to a common platform by adopting the percentage of occurrence methodology based on the number of scintillation events for future studies.